Umrah Service Strategy Based on Experiential Marketing (Case Study of Amana Tour and Travel, Yogyakarta) - M. Zikrullah Fifnanda; Aris Risdiana; Reza Bakhtiar Ramadhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
The purpose of this research is to know the experiential marketing strategy for the development of experience and to maintain the customer experience in Amana Tour & Travel Yogyakarta. Marketing a product essentially needs to know the sustainability and resilience of products on the market. Considering the mushrooming service providers that mushroomed umrah, needed a strategy to win the competition in a healthy manner. In addition, this strategy is used to provide a good experience in the minds of customers and certainly able to maintain and enhance the experience. After doing research, it can be seen that the strategy of experiential marketing in Amana Tour & Travel Yogyakarta in general is to change the negative stigma of Umrah travel agency that currently exists. This is done by Amana Tour & Travel through 3 ways of building a good and solid brand architecture, presenting and maintaining good customer experience, and bridging the presence of customer experience using experience providers. For the development of customer experience and strategies to maintain it, Amana Tour & Travel applies the principle with a flowing system. This principle emphasizes the convenience and convenience of customers in a variety of services both when registering, when on board, and upon arrival in Indonesia. Amana Tour & Travel also applies kinship system with the pilgrims by doing the best possible communication, one of them is by conducting holy worship which also involves the public